Elevating Teacher Effectiveness:The Role of Spirituality in the Four Levels of Classroom Leadership - Masduki Asbari (International Journal of Management and Economic Research (IJOMER), 2024)
This study utilizes a descriptive qualitative methodology, employing participatory observation, interviews, and document analysis to collect data. The research involves educators teaching across diverse educational levels, ranging from primary to secondary education. The results identify four levels of teacher performance within the context of classroom leadership, focusing on interpersonal relationships with students, colleagues, and the wider learning community. The progression starts with Level R1 (Right) teachers, who strictly adhere to directives or assignments. Level R2 (Relationship) teachers are distinguished by their strong emotional connections with students, colleagues, and other members of the learning community. Level R3 (Respect) teachers earn respect from students, colleagues, and others in the learning community through their exemplary conduct. Level R4 (Result) teachers excel in enhancing their students' dignity based on their unique talents. The journey to advancing teacher leadership from R1 to R4 involves elements such as nurturing, role modeling, and coaching. Furthermore, the essential role of spiritual energy in enabling teachers to continuously elevate their performance levels is underscored. The study highlights the importance of robust interpersonal relationships in shaping teacher effectiveness and its broader impact on improving the overall quality of education.